Value of Office-Based Labs to an Interventional Radiology Practice - Lee, Shimwoo; Srinivasa, Ravi N.; Patel, Prital; Genshaft, Scott; Enzmann, Dieter R. (Journal of Clinical Interventional Radiology ISVIR, 2022)
Purpose Office-based laboratories (OBLs), or outpatient interventional suites, are rapidly gaining traction with both patients and interventionalists. Compared with hospitals, OBLs can provide greater convenience for patients, allow physicians greater autonomy, and potentially generate more revenue under a lower cost structure. The aim of this article is to discuss logistics and finances of running an OBL using the authors' institution as a guide for interventional radiologists seeking to establish their own OBL.Materials and Methods Interventional radiology (IR) procedures performed at an OBL from the authors' academic institution were reviewed from January 2017 to December 2020. Yearly revenues and expenses related to IR procedures were recorded.Results The number and complexity of IR procedures performed in the OBL increased over time with nearly 10-fold growth of revenue from 2017 to 2020.Conclusion Most IR procedures performed in the hospital are feasible in the OBL setting, and by increasing patient volume and variety over time, an individual OBL can develop into a robust patient care center capable of generating revenue.
Keywords: office-based; laboratory; interventional; radiology